2015
DOI: 10.3400/avd.oa.14-00137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Clinical Outcomes after Drug-Eluting Stent Implantation in Patients with Coronary Artery Disease with and without Prior Cerebral Infarction

Abstract: Objective: To compare the clinical and angiographic outcomes after implantation of drug-eluting stents (DESs) in patients with coronary artery disease (CAD) with or without prior cerebral infarction. Materials and Methods: Ninety-eight consecutive patients (130 lesions) who underwent successful coronary DES implantation were prospectively classified into two groups: those with a clinical history of symptomatic cerebral infarction (cerebral infarction group, 49 patients, 69 lesions) and those without a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…9,21 Whereas, Zhang et al and Sasao et al found no significant differences in rates of post-PCI stroke in patients with and without a history of TIA or stroke. 7,8 Our findings underscore the importance of appropriately counseling patients with a history of TIA or stroke on the risks of post-PCI in-hospital stroke. An open conversation of patient-specific risks and benefits of PCI is integral to the process of shared decision-making.…”
Section: Discussionmentioning
confidence: 66%
“…9,21 Whereas, Zhang et al and Sasao et al found no significant differences in rates of post-PCI stroke in patients with and without a history of TIA or stroke. 7,8 Our findings underscore the importance of appropriately counseling patients with a history of TIA or stroke on the risks of post-PCI in-hospital stroke. An open conversation of patient-specific risks and benefits of PCI is integral to the process of shared decision-making.…”
Section: Discussionmentioning
confidence: 66%
“…However, recent studies have shown that CABG only increased the risk of perioperative stroke, while the rate of long-term stroke was comparable between PCI and CABG [7,[18][19][20][21]. Moreover, as aforementioned, patients with prior CEVD, who have complex and diffuse CAD and multiple comorbidities, and who undergo PCI may experience increased rates of recurrent cerebrovascular events, myocardial infarction, and death9, [16,22]. It is important to balance the risk of stroke, which represents the major adverse event of CABG, against the risk of other adverse events such as repeat revascularization, myocardial infarction and death, when determining the optimal revascularization modality between CABG and PCI in patients with prior CEVD [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The findings from previous studies that have involved DES in CAD have shown reductions in the incidence of cardiac events associated with recurrent ischemia and lower rates of angiographic restenosis compared with bare metal stents ( 19 , 20 ). However, Sasao et al ( 21 ) reported that the long-term clinical outcomes were worse in patients with CAD who had experienced previous cerebral infarctions compared with those who had not experienced previous cerebral infarctions. Patients with cerebral infarction typically had motor dysfunction and could not perform a sufficient exercise stress test for assessment of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%